Better evidence for earlier assessment and surgical intervention for refractory epilepsy (The BEST study): a mixed methods study protocol. Issue 8 (21st August 2017) - Rapport, Frances; Shih, Patti; Mitchell, Rebecca; Nikpour, Armin; Bleasel, Andrew; Herkes, Geoffrey; Vagholkar, Sanjyot; Mumford, Virginia
Abstract : Introduction: One-third of patients with refractory epilepsy may be candidates for resective surgery, which can lead to positive clinical outcomes if efficiently managed. In Australia, there is currently between a 6-month and 2-year delay for patients who are candidates for respective epilepsy surgery from the point of referral for surgical assessment to the eventual surgical intervention. This is a major challenge for implementation of effective treatment for individuals who could potentially benefit from surgery. This study examines implications of delays following the point of eligibility for surgery, in the assessment and treatment of patients, and the factors causing treatment delays. Methods and analysis: Mixed methods design: Observations of qualitative consultations, patient and healthcare professional interviews, and health-related quality of life assessments for a group of 10 patients and six healthcare professionals (group 1); quantitative retrospective medical records' reviews examining longitudinal outcomes for 50 patients assessed for, or undergoing, resective surgery between 2014 and 2016 (group 2); retrospective epidemiological study of all individuals hospitalised with a diagnosis of epilepsy in New South Wales (NSW) in the last 5 years (2012–2016; approximately 11 000 hospitalisations per year, total 55 000), examining health services' use and treatment for individuals with epilepsy, including refractory surgery outcomes (group 3). Ethics and dissemination: Ethical approval has been granted by the North Sydney Local Health District Human Research Ethics Committee (HREC/17/HAWKE/22) and the NSW Population & Health Services Research Ethics Committee (HREC/16/CIPHS/1). Results will be disseminated through publications, reports and conference presentations to patients and families, health professionals and researchers.